Bivalirudin anticoagulation to overcome heparin resistance in a neonate with cerebral sinovenus thrombosis. Issue 1 (January 2020) - Bertamino, Marta; Severino, Mariasavina; Parodi, Alessandro; Andreato, Chiara; Malova, Mariya; Svahn, Johanna; Tortora, Domenico; Moretti, Paolo; Molinari, Angelo C.; Ramenghi, Luca A.
Abstract : N/A: Anticoagulation in a neonate is a challenge and the availability of anticoagulant options is extremely limited. Here we describe the use of a direct thrombin inhibitor, bivalirudin, in a full-term neonate with symptomatic cerebral sinovenous thrombosis complicated by bilateral thalamic hemorrhagic stroke and intraventricular hemorrhage, who could not be effectively treated with sodium heparin due to heparin resistance (HR) and showed thrombosis regression after start of bivalirudin treatment, without worsening of the hemorrhage. While the use of bivalirudin in neonates has been previously described, the indication of cerebral sinovenous thrombosis and the setting of HR are unique.